2022
DOI: 10.1038/s41389-022-00378-7
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 confers chemoresistance through activating PI3K

Abstract: Circumventing chemoresistance is crucial for effectively treating cancer including glioblastoma, a lethal brain cancer. The gap junction protein connexin 43 (Cx43) renders glioblastoma resistant to chemotherapy; however, targeting Cx43 is difficult because mechanisms underlying Cx43-mediated chemoresistance remain elusive. Here we report that Cx43, but not other connexins, is highly expressed in a subpopulation of glioblastoma and Cx43 mRNA levels strongly correlate with poor prognosis and chemoresistance in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 77 publications
2
27
0
Order By: Relevance
“…Cx43 is a component of gap junctions that are responsible in part for intercellular communication. Recent studies have indicated that Cx43 controls the response of GBM cells to TMZ through various mechanisms, such as modulating mitochondrial apoptosis, and activating P13K signaling (Gielen et al, 2013; Munoz et al, 2014; Pridham et al, 2022). Pridham et al (2022) have shown that expression of Cx43 protein in high‐grade glioma is higher than other connexins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cx43 is a component of gap junctions that are responsible in part for intercellular communication. Recent studies have indicated that Cx43 controls the response of GBM cells to TMZ through various mechanisms, such as modulating mitochondrial apoptosis, and activating P13K signaling (Gielen et al, 2013; Munoz et al, 2014; Pridham et al, 2022). Pridham et al (2022) have shown that expression of Cx43 protein in high‐grade glioma is higher than other connexins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that Cx43 controls the response of GBM cells to TMZ through various mechanisms, such as modulating mitochondrial apoptosis, and activating P13K signaling (Gielen et al, 2013; Munoz et al, 2014; Pridham et al, 2022). Pridham et al (2022) have shown that expression of Cx43 protein in high‐grade glioma is higher than other connexins. They also show that high levels of Cx43 messenger RNA were associated with poor prognosis of GBM patients (Pridham et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PI3K/AKT leads to direct phosphorylation of multiple glycolysis enzymes to promote glucose utilization, but can also activate alternative pathways in the absence of glucose [ 249 , 250 , 251 ]. Connexins have been implicated within these signal transduction pathways, including many aspects related to cancer cell function such as motility, invasion, proliferation and therapy resistance [ 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 ]. Ongoing studies drawing connections between these growth promoting pathways and their effects on connexins, will undoubtedly continue to converge on metabolic involvement.…”
Section: Emerging Connectionsmentioning
confidence: 99%
“…Supporting this, the pan-PI3K inhibitor, PX-866, has been found to block TMZ-induced autophagy, whilst promoting GBM cell death ( 103 ). In addition, the activation of PTEN/PI3K/AKT signaling has been reported to be an essential step in the development of TMZ resistance in GBM cells in a MGMT-dependent manner ( 104 - 106 ).…”
Section: Oncogenic Lncrnas Promote Tmz Resistance In Gliomasmentioning
confidence: 99%